Optimalisasi Peran Mahasiswa Dalam Penguatan 4 Keterampilan Bahasa Melalui Materi Adverb Of Frequency Bagi Siswa MTS Hidayatul Insan Palangka Raya - Syarif Hidayat; Zaitun Qamariah; Hesty Widiastuty (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The collaborative community service activity between the lecturers and students at MTs Hidayatul Insan aims to enhance the learning experience and academic support for students under the title